Ensaios toxicológicos, não clínico e clínicos fase I e II, com o antiviral tópico celodenina no tratamento de herpes labial recorrente - Cunha, Mônica Lorena Dias Meirelles da (2014)
Herpes simplex labialis, one of the most prevalent viral infections worldwide, is a chronic, relapsing incurable disease, persist throughout the lifetime of the host, usually in a latent form. Facing the difficulty of finding an effective therapy to traditional medicine, we seek new possibilities in complementary medicine treatment for this condition. The study aimed to perform non-clinical and clinical phase I and II toxicological tests with topical antiviral celodenina, neoflavonide synthesized from the ethanol extract of the stem bark of Coutarea hexandra (Jacq) K. Shum, topically. Preclinical studies have evaluated the dermal primary skin irritation - acute effect (single dose) and acute eye irritation (single dose) and in both experiments albino rabbits Zealanders, healthy adults were used in number 12, being 6 males and 6 females (control and treated) at a dose of 0.5 g of the cream. The assessment of primary skin irritation demonstrated that the cream does not irritate the skin of rabbits tested in Drug Testing Laboratory of the Federal University of Paraíba, since none showed any degree of erythema and edema throughout the experiment. Regarding eye irritation simple, cream showed low irritant effect, as only 33.3% rabbits showed redness in conjunctiva during the first 24 hours after application of the test substance. Did not identify any changes in the iris and cornea, in any animal throughout the experiment. To investigate the clinical phase I toxicity in humans, the celodenina, 30 volunteers were selected, of both sexes, clinically healthy, aged between 18 and 65 years. Study participants were treated daily, the night shift, by dermal route, with the cream for a period of four weeks and evaluated before the start of the study and after its termination hematology (CBC), biochemical (glucose, urea, creatinine, total cholesterol, AST, ALT, alkaline phosphatase), in order to detect possible changes resulting from use of cream in them, as well as to compare the results before and after the study. No abnormal values for both hematological variables as for biochemical between times and groups were highlighted. During treatment with the cream, some adverse reactions were observed in participants: local dryness (7%), burning (13%), tingling (7%) and erythema (7%), but the number of affected subjects was small, and symptoms and signs reported occurred in the first week of the study, not requiring specific treatment, disappearing spontaneously. Clinical phase II trials were randomized, double-blind, comparing celodenina 4% with placebo in 33 patients with recurrent herpes labialis between 18 and 65 years, who used these substances three times daily for 15 days. Patients were also assessed before and after the study of hematological and biochemical tests, which showed no significant values between times. Few adverse effects were reported, burning (21%) and local dryness (5.3%), both mildly during the first 30 minutes after application in the first five days. Herpes recurrences were evaluated for 30, 60 and 90 days and the participants treated with celodenina 4% had lower percentage of same relative to placebo at all time. These results suggest a low toxicity of the product, satisfactorily efficient control of relapses and indicate that this formulation can be used in Phase III clinical trials, dose and route of administration tested in the treatment of recurrent herpes labialis.